Severe Diabetic Gastroparesis: Diagnosis by Ruling out of Constitutional Syndrome in an Older Adult: a Case Report - Vianey Guadalupe Téllez Bolaños; Louis Fernando Robles Fernandes (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Diabetic gastroparesis represents one of the complications associated with long-standing diabetes that leads to the development of various nutritional conditions that increase the morbidity and mortality of patients. It is characterized by delayed gastric emptying, and consequently, decreased nutritional absorption, as well as intolerance to the oral route due to manifestations suggestive of intestinal obstruction due to accumulation of food. Its diagnosis is confirmed by evidence of delayed emptying by scintigraphy and its treatment involves prokinetics, antiemetics, and even surgical procedures. We present the case of a 75-year-old male patient who, after the directed and intentional ruling out of obstructive pathology as an initial suspicion in view of the presented condition, was diagnosed with severe diabetic gastroparesis. Findings of the diagnostic approach implemented in the case are described and a literature review is performed. The presentation of this case is important because it is extremely important to describe the diagnostic tools to be implemented to make a timely confirmatory diagnosis of this condition.